2018
DOI: 10.1001/jamaneurol.2017.4907
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Amyloid and Tau Accumulation in Young Adults With Autosomal Dominant Alzheimer Disease

Abstract: IMPORTANCE It is critically important to improve our ability to diagnose and track Alzheimer disease (AD) as early as possible. Individuals with autosomal dominant forms of AD can provide clues as to which and when biological changes are reliably present prior to the onset of clinical symptoms. OBJECTIVE To characterize the associations between amyloid and tau deposits in the brains of cognitively unimpaired and impaired carriers of presenilin 1 (PSEN1) E280A mutation. DESIGN, SETTING, AND PARTICIPANTS In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
173
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(199 citation statements)
references
References 39 publications
19
173
2
Order By: Relevance
“…Aβ 1–42 aggregation was most evident in the anterior cingulate and precuneus [36]. Consistent with this initial study, a recent report using the Pittsburgh-compound-B (PiB) tracer showed cortical Aβ 1–42 aggregation beginning in carriers with an average of −15 EYO [37]. Flortaucipir PET imaging of tau in the brain of carriers has shown progressive accumulation of tau in the entorhinal cortex and inferior temporal lobe an average of −6 EYO, and an estimated 10 years after the first evidence of cortical Aβ 1–42 [37].…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Aβ 1–42 aggregation was most evident in the anterior cingulate and precuneus [36]. Consistent with this initial study, a recent report using the Pittsburgh-compound-B (PiB) tracer showed cortical Aβ 1–42 aggregation beginning in carriers with an average of −15 EYO [37]. Flortaucipir PET imaging of tau in the brain of carriers has shown progressive accumulation of tau in the entorhinal cortex and inferior temporal lobe an average of −6 EYO, and an estimated 10 years after the first evidence of cortical Aβ 1–42 [37].…”
Section: Resultssupporting
confidence: 61%
“…The right visuo-perceptual area, which showed greater activity in younger carriers, was conversely found to have decreased activity in carriers close to clinical onset [29]. In the context of other markers of AD, the change from EEG-measured cortical hyperactivity to hypoactivity in PSEN1 E280A carriers appeared to coincide with elevated levels of in vivo cortical Aβ 1–42 in mutation carriers [36,37]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the current understanding of AD, Aβ deposition begins years, if not decades, before the clinical symptoms of cognitive decline, which are directly caused by neurodegeneration, and tau accumulation happens in between the two (C. R. Jack, Jr. et al, 2013; Quiroz et al, 2018). Therefore, the natural continuation of this research will be to gather longitudinal data and integrate the current findings with the temporal associations between protein accumulation, atrophy, hypometabolism and white matter disruption.…”
Section: Discussionmentioning
confidence: 99%